SAE Technical Paper Series 2006
DOI: 10.4271/2006-01-2341
|View full text |Cite
|
Sign up to set email alerts
|

Environment-Aware Postural Control of Virtual Humans for Real-time Applications

Abstract: Interactive control of a virtual character through full body movement has a wide range of applications. However, there is a need for systems that accurately reproduce the motion of a performer while accounting for surrounding obstacles. We propose an approach based on an efficient Prioritized Inverse Kinematics constraint solver. The inputs to the system are the acquired positions of relevant body parts. These positions are tracked by the virtual character thanks to a set of kinematic constraints. At the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Our method employs a different approach to Inverse Kinematics, since user-defined sets of joints can be used for the satisfaction of each constraint, and since a different priority can be assigned to each constraint. This has been used in the past in specific contexts, like offline reconstruction of motions from a database where only a reduced subset of the input markers is known [Peinado et al 2006]. In this work we extend this approach to online avatar control from a set of markers which is smaller (and thus less encumbering) than most production setups, yet at the same time allowing for an accurate reconstruction of postures.…”
Section: Full-body Avatar Controlmentioning
confidence: 97%
“…Our method employs a different approach to Inverse Kinematics, since user-defined sets of joints can be used for the satisfaction of each constraint, and since a different priority can be assigned to each constraint. This has been used in the past in specific contexts, like offline reconstruction of motions from a database where only a reduced subset of the input markers is known [Peinado et al 2006]. In this work we extend this approach to online avatar control from a set of markers which is smaller (and thus less encumbering) than most production setups, yet at the same time allowing for an accurate reconstruction of postures.…”
Section: Full-body Avatar Controlmentioning
confidence: 97%
“…Nevertheless, these methods do not take into consideration the limb con- straints a multibody system is subject to for repositioning in case of self-collision. The strategy to avoid self-collisions must be integrated within the IK algorithm as it is shown in the works of Kallmann [47] and Peinado et al [48]. In the present study we integrate a strategy to reorient the upper arms in the SIK method as shown in Algorithm 5.…”
Section: Self-collisions Avoidancementioning
confidence: 99%